Case Report: Functional investigation of the γENaC G532S mutation presenting as mild PHA-1B3 - Centonze, Eleonora; Girish, Meenakshi; van Bemmelen, Miguel Xavier; Staub, Olivier; Subramaniam, Girish; Kellenberger, Stephan (Frontiers in Medicine, 2025)
Pseudohypoaldosteronism type 1 (PHA-1) is a rare genetic disease caused by aldosterone resistance, characterized by severe sodium loss, hyperkalemia, dehydration, and vomiting. The Epithelial Na+ Channel (ENaC) is a cation channel that constitutes the rate-limiting step of transepithelial Na+ transport in many tissues and regulates blood volume and pressure. Mutations in any of its subunits (α, β, or γ) have been shown to cause PHA-1B. The present investigation is a case study of a 4-month-old female born to consanguineous parents with symptoms suggestive of a form of PHA-1. The child presented with failure to thrive, accompanied by mild hyponatremia and hyperkalemia, together with a normal anion gap metabolic acidosis. Whole exome sequencing, conducted to identify genetic variants, revealed a variant of uncertain significance, the homozygous missense mutation c.1594G > A, p. Gly532Ser in the SCNN1G gene, associated with PHA-1B3. To investigate the functional impact of this mutation, in vitro electrophysiological and biochemical studies were performed with wild type αβγ and mutant αβγG532S-ENaC. This analysis showed that the γG532S mutation reduced, but did not suppress ENaC expression and activity. The functional observation explains the mild phenotype of this novel SCNN1G mutation, which contrasts with the typically severe presentation of autosomal recessive PHA-1B. In our case, the patient showed a positive clinical response to sodium chloride supplementation alone. These findings suggest that certain missense mutations in SCNN1G may result in a milder disease course, underscoring the importance of functional studies in understanding genotype–phenotype correlations in PHA-1.